Social Network Analysis research in Library and Information Sciences: a cocitation and co-words analysis - Gálvez, Carmen (Revista General de Información y Documentación, 2018)
The objective of this work was to explore and visualize the intellectual and cognitive structure of Social Network Analysis (SNA) research, within the scientific area of Library and Information Sciences (LIS). The applied methodology combined co-citation and co-words analysis. The data was obtained from the scientific publications indexed in the Web of Science (WoS) database. We identified a total of 383 publications, related to SNA in LIS, during the period 2008- 2017. The analysis of co-citation of sources evidenced the high level of transversality and the marked interdisciplinary nature of SNA, the most relevant journals were Scientometrics and Journal of the American Society for Information Science and Technology. The co-citation analysis of documents identified the theoretical basis and founding documents of the SNA, highlighting the works of Wasserman and Faust (1994), Freeman (1979), Watts and Strogatz (1998), Otte and Rousseau (2002). The co-citation analysis of authors revealed the different schools and academic networks, standing out authors such as S.P. Borgatti, R.S. Burt, M. E. J. Newman, S. Wasserman, K. Faust, L.C. Freeman, M. Callon and L. Leydesdorff. On the other hand, the co-words analysis showed the main research fronts: i) evaluation of the impact of the scientific activity; ii) application of network analysis to Social Media; iii) scientific collaboration networks, co-authorship networks and co-words networks; and iv) knowledge networks.